August von Cieszkowski: The Philosophy of History or From the philosophy of thought (Theory) to the philosophy of action (Praxis) - khechai, abdenour (Journal of Social Sciences and Humanities, 2024)
Sieszkowski's philosophy of history determines the mental course of history in the future, and from it we can make a comprehensive plan for history in the future. History is not only the past and the present, as Hegel sees it, but also the future, that is, the future of free humanity Hegelian philosophy, according to Cieszkowski, depends on the present and has no effect on human destiny Where Sieszkowski emphasizes the continuous and continuous movement of dialectics, which directs his thought towards the future instead of the past as Hegel did. Because one of the most important defects of Hegel's philosophy is that it is limited to the past only and extracts the laws of history from the past only, but true history, according to Sieszkowski, is what includes the past and the future. If Hegel divided world history into the Eastern world, the Greco-Roman world, and the Germanic Christian world: on the other hand, Cieszkowski proposes a contrasting division based on: (1) antiquity, (2) Christianity, (3) the future in which antiquity was characterized by feeling and Christianity. Therefore, Sieszkowski's philosophy of history aims to replace the speculative Hegelian philosophy that has no effect on human destinies with a philosophy of action and a philosophy of socially directed, revolutionary practical activity that is based on the laws of history in order to develop the world and in order to change the world. We must also rely on the laws of historical development and deduce from the past and present general plans for the future in order to rationally target human activity and control the course of history on the basis of that, because the future role of philosophy is to be a practical philosophy. Hence, Sieszkowski transferred the movement of dialectic from the present to the future. Since history does not stop and is characterized by continuity and permanence, this division presented by Hegel cannot be appropriate and compatible with dialectics. According to Sieszkowski, strict dialectics must be applied to the philosophy of history, which Hegel did not do, and Hegel did not mention the future in his work at all. The philosophy of work is a philosophy that concerns applied action because the future is the fundamental goal of philosophy, as well as socially directed activity and action (praxis).The philosophy of action that Sieszkowski came up with is a philosophy that pushes man to create the future. The philosophy of action also allows man to assist the history of the world instead of being its unconscious tool. The importance of his philosophy also lies in his tendency towards interest in immanence and materialism, which will be very central in Feuerbach’s thought, as well as the focus on the practical application of Praxis that characterizes Marx’s thought. Sieszkowski’s philosophy also had a great influence on Moses Hesse, Bakunin, and Herzen